PRE- AND PRO-IMPLANT PREPARATIONS ARE THEY THE KEY TO SUCCESS? - Cristian Schiller; Alexandru Ciorcila; Silvia Pascu; Marc Hage-Moussa; Cristina Dascalu; Ionut Zaharii; Norina Consuela Forna (Romanian Dental Association for Education, 2022)
The purpose of this study is to highlight the necessity of pre-implant treatment for long term success. Pre-implant treatment is essential in rehabilitating the oral cavity and preparing the future implant site, from assessing the periodontal health of the patient to bone augmentation procedures. These preparations are of utmost importance and involves interdisciplinary collaboration from a whole team with different specialties. Dental implant treatment isn't the purpose of the patient's visit, instead it's just a tool that the dentist uses to achieve full oral rehabilitation amongst others such as periodontal, endodontic, orthodontic, surgical (extraction, bone augmentation, sinus elevation) and prosthetic treatments, reestablishing masticatory function and comfort to the patient. We can assert that the pre- and pro-implant preparations are certainly the key to success in full mouth rehabilitation and implant treatment.